2016
DOI: 10.1093/ajh/hpw128
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptors, Hypertension, and an Antimalarial Drug

Abstract: The role of the immune system in the pathogenesis of hypertension is a growing area of research. Although the immune system had long been suspected to contribute to hypertension, only in the last decade have studies begun to define the roles of the participating immune cells and molecules involved in hypertension. [1][2][3][4] Toll-like receptors (TLRs) 5,6 are part of the innate immune system that recognize molecular patterns on various pathogens (pathogen-associated molecular patterns) and so called endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“… 61 TLR1 or TLR6 LDLr–/– mice model (TLR2 has linkage with TLRs 1 and 6 in signal transmission, the model is used to identify the co-receptor of TLR2 involved in TLR2 mediated atherosclerosis) Although, depleting (TLRs 1 and 6) showed no effect on development of lesion without exogenous agonists, deficiency of TLRs 1 and 6 reduce the progression of atherosclerosis with exogenous TLR1 and TLR6 ligands, respectively (probably due to response of TLRs 1 and 6 for unidentified endogenous TLR2 ligands). 81 In Apo lipoprotein E–/– mice model Reduced TLR2 showed protection in the formation of aortic atherosclerotic plaque, might be because of reduced lipid aggregation and macrophage entry to aortic sinus in addition to decreed monocyte chemoattractant protein-1 (MCP-1) levels 82 Hypercholesterolemia rabbit model In the aorta, it was observed that mRNA expression of TLR3 was highly upregulated 83 In mice (wild type) and intact TLR3 Function of ECs was impaired due to systemic administration of TLR3 agonists 84 In mice model with LDLr–/– TLR 3 deficit in hematopoietic cells produces protection from the generation of atherosclerosis while the level of circulating lipids are unchanged 85 In Apo lipoprotein E–/– mice model TLR3 showed protection against arterial injury and atherogenesis while depletion of the receptor enhances formation of atherosclerosis 86 In mice with TLR3 deficiency It was observed that the amount of collagen and SMS was raised in the lesion of atherosclerosis implying the contribution of TLR3 to cause disturbance in the area of plaque due to partial controlling of the function of MMP-2 and MMP-9 in macrophages. 87 In human platelet It was showed that TLR3 in human platelet can promotes the aggregation of platelet, release of ATP release, and stimulation of integrin.…”
Section: Tlrs and Diabetic Complicationsmentioning
confidence: 99%
“… 61 TLR1 or TLR6 LDLr–/– mice model (TLR2 has linkage with TLRs 1 and 6 in signal transmission, the model is used to identify the co-receptor of TLR2 involved in TLR2 mediated atherosclerosis) Although, depleting (TLRs 1 and 6) showed no effect on development of lesion without exogenous agonists, deficiency of TLRs 1 and 6 reduce the progression of atherosclerosis with exogenous TLR1 and TLR6 ligands, respectively (probably due to response of TLRs 1 and 6 for unidentified endogenous TLR2 ligands). 81 In Apo lipoprotein E–/– mice model Reduced TLR2 showed protection in the formation of aortic atherosclerotic plaque, might be because of reduced lipid aggregation and macrophage entry to aortic sinus in addition to decreed monocyte chemoattractant protein-1 (MCP-1) levels 82 Hypercholesterolemia rabbit model In the aorta, it was observed that mRNA expression of TLR3 was highly upregulated 83 In mice (wild type) and intact TLR3 Function of ECs was impaired due to systemic administration of TLR3 agonists 84 In mice model with LDLr–/– TLR 3 deficit in hematopoietic cells produces protection from the generation of atherosclerosis while the level of circulating lipids are unchanged 85 In Apo lipoprotein E–/– mice model TLR3 showed protection against arterial injury and atherogenesis while depletion of the receptor enhances formation of atherosclerosis 86 In mice with TLR3 deficiency It was observed that the amount of collagen and SMS was raised in the lesion of atherosclerosis implying the contribution of TLR3 to cause disturbance in the area of plaque due to partial controlling of the function of MMP-2 and MMP-9 in macrophages. 87 In human platelet It was showed that TLR3 in human platelet can promotes the aggregation of platelet, release of ATP release, and stimulation of integrin.…”
Section: Tlrs and Diabetic Complicationsmentioning
confidence: 99%